Options and socio-technical dilemmas in Argentinian energy developments: the smart grid project in the city of General San Martín, Mendoza (Huellas, 2020)
The possibility of having cleaner and more sustainable energy networks, as well as reducing the consequences of climate change, promotes transitions towards efficient energy matrices based on renewable energy. The diffusion of ICT, the most efficient use of energy and the promotion of distributed energy generation advances in different territorial scales. Within this framework, Smart Electrical Grids (SEGs), which combine traditional electricity supply with ICT, constitute a new way of organizing the flows of electricity and of information based on the integration of data from the various nodes of the energy network. This paper explores the socio-technical changes of a case of smart grids in the province of Mendoza on the basis of observations and semi-structured interviews in the localities involved. From the perspective of the social studies of technology, the normative antecedents of distributed energy generation and smart grids (SEGs) are investigated as well as the process of transformation of the “user / consumer” to the “user / generator”. Smart grids enable the incorporation of renewable energy as well as favoring territorial expansion into marginal regions while promoting an eventual advance towards a national sustainable energy system.
Keywords: energy; networks; territory; technologies